1997
DOI: 10.1152/ajpheart.1997.272.5.h2327
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nitric oxide, superoxide, and peroxynitrite in myocardial ischemia-reperfusion injury in rats

Abstract: In the present study, the contribution of nitric oxide (NO), superoxide, and peroxynitrite to the inflammatory response induced by myocardial ischemia-reperfusion (MI/R) was investigated. Male Sprague-Dawley rats were anesthetized, and the left main coronary artery was ligated for 20 min and reperfused for 5 h. MI/R induced severe arrhythmias, indicated by a significantly elevated arrhythmia score in the MI/R group compared with that in the sham control group. Creatine kinase activity in the left ventricular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
136
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(140 citation statements)
references
References 0 publications
3
136
0
1
Order By: Relevance
“…and subsequent inactivation has been reported (Zou and Bachschmid, 1999d), and which has been associated with endothelial dysfunction in atherosclerosis and ischemiareperfusion damage (Liu et al, 1997). The analysis presented here sets the basis for future studies in the field of vascular aging, in particular for those aimed at preventing age-related vascular dysfunction.…”
Section: -12mentioning
confidence: 70%
“…and subsequent inactivation has been reported (Zou and Bachschmid, 1999d), and which has been associated with endothelial dysfunction in atherosclerosis and ischemiareperfusion damage (Liu et al, 1997). The analysis presented here sets the basis for future studies in the field of vascular aging, in particular for those aimed at preventing age-related vascular dysfunction.…”
Section: -12mentioning
confidence: 70%
“…During NO synthesis by NOS, if L-arginine levels decrease or consumption of NO increases via cell-free plasma hemoglobin and ROS, then oxidative damage occurs, HbS denatures, and superoxide production increases. It was shown that iNOS inhibition significantly limits tissue ischemiareperfusion injury in the liver and kidneys [10][11]; however, inhibition of iNOS attenuated ischemiareperfusion injury in the rat heart [12], but not in the rat lung [13]. Increased iNOS expression was reported in the kidneys of transgenic mice [9], but Nath et al [14] reported the lack of iNOS upregulation in intrarenal vasculature and increased iNOS expression in the glomeruli and distal tubules of sickle mice.…”
Section: Discussionmentioning
confidence: 99%
“…Increased iNOS expression and a consequent increase in tissue nitrite and nitrate production have been observed in the kidneys and liver of SCD patients [8], mice [2,3,8,9], and pigs [4]. Additionally, it was shown that iNOS inhibition significantly limits tissue ischemia-reperfusion injury in the liver and kidneys [10,11]; however, inhibition of iNOS attenuated ischemia-reperfusion injury in the rat heart [12] and did not affect ischemia-reperfusion injury in the rat lung [13]. Increased levels of iNOS expression were shown in the kidneys of transgenic mice [9], but Nath et al [14] reported the lack of upregulation of iNOS in the intrarenal vasculature and increased expression of iNOS in the [15][16][17] and in vitro [18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is hypothesized that this molecule determines the role of NO in either physiologic vs pathologic processes [3], as many of the pathological effects of NO are mediated by PN [3,[6][7][8]. These pathologic effects of PN are discussed in excellent reviews elsewhere [3,[9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%